Analisis Internal Perusahaan (Strength & Weakness), Menggunakan konsep âResource-Based View of the Firmâ dengan Kerangka VRIO - Wandrial, Son (Bina Nusantara University, 2011)
Problems in the companys internal environmental analysis is to determine the strengths andÂ weaknesses (internal resources), we did not have reasonable grounds to determine whether the companysÂ internal resources as a strength or weakness. Before we can determine whether a resource can be categorized asÂ strengths or weaknesses, we must have a certain criteria so that appropriate resources are said to be a strengthÂ or weakness